HUBUNGAN PERSEPSI IBU BALITA TENTANG POSYANDU DENGAN PEMANFAATAN POSYANDU MAWAR 2 RW 06 KEBAGUSAN JAKARTA SELATAN TAHUN 2015 - Septifani, Alifa Dinda; Apriningsih, Apriningsih (Fakultas Ilmu Kesehatan, 2015)
Posyandu was one manifestation of Health Efforts on Community Based (UKBM). Based on data Posyandu Mawar 2 in February 2015 there were a decreased number of mothers’s visit from 81.25% to 62.5%, so the researchers wanted to know about association of the mother’s perception with the utilization of The Posyandu. This research used cross sectional study design using total sampling (80 mothers). Data collection was done by direct interviews based on the questionnaire and analyzed using Chi Square. The result there’s a significant association between mother’ss perception of the distance to the utilization of Posyandu RW 06 Posyandu Mawar 2 Kebagusan South Jakarta and there’s no significant relationship between education, employment and the knowledge and mothers’perceptions about the completeness of facilities, the attitude of cadres and the presence of health workers. Suggestions for Posyandu is to increase of mother’confident to visit Posyandu